xmnk xk+1
³ xmnk.
:
xmnk+2
= min (xk+2, min (k+1, k)) = Min (k+2,
k+1, k).
, xk , ..., xi
mni = Min (k, ..., i).
. i = k + 1, k + 2 ­. , (i + 1)- . , :
xi+1
i+1 < xmni = min(xi+1, mni)
mni+1
=
mni i+1 ³ mni = min(xi+1, xmni)
= min (xi+1, Min (k , ..., i)) = Min (k, ..., i, xi+1).
. , ­ ­ :
xmnN
= Min (xk, ...,
N)
.
2.

{ xmn = Min (k, ..., N) }
xi¢mn= xk

k' = Min (k, ..., N).
. 1 xmn = Min (xk, ..., N). k' =
xmn,
k' = xmn = Min (k, ..., N).
.
. 1', ..., N', ­ 1' £ 2' £ ... £ N'.
. :


k = 1 N - 1
xmn
:= k
............... { xmn = Min (k, ..., i) }
¢k
= xmnN

= k
렠 { k' = Min (k, ..., N) }
{ 1' £ 2' £ ... £ k' }